THE EFFECT OF EMPLOYER BRANDING AND WORK EXPERIENCE ON EMPLOYEE RETENTION AT PT TANTO INTIM LINE JAKARTA - Raruna, Tegarini Woro Cita; Jaya, Umban Adi (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyze the influence of employer branding and work experience on employee retention at PT Tanto Intim Line Jakarta. The research background indicates that, in the era of globalization, companies face intense competition, making human resource management, particularly employee retention, crucial for achieving organizational goals and avoiding declines in employee performance due to turnover. Employer branding and work experience are identified as essential factors influencing employees' decisions to stay within an organization. This research method uses a quantitative approach, with a case study of employees at PT Tanto Intim Line Jakarta. The research population consists of all 100 employees of PT Tanto Intim Line. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the validity and reliability tests show that all research instruments are valid and reliable. The research results indicate that employer branding has a significant positive partial effect on employer retention. Similarly, work experience also has a significant positive partial effect on employer retention. Furthermore, simultaneously, employer branding and work experience have a significant effect on employer retention. These two variables account for 12.8% of employer retention, while factors outside the research model account for the remaining 87.2%. This research provides an in-depth understanding of the importance of both factors in retaining competent employees.